Abstracts of Symposium I: Stable Coronary Artery Disease: The Stable Plaque - Symposium I: Stable Coronary Artery Disease: The Stable Plaque (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Abstracts of Symposium I: Stable Coronary Artery Disease: The Stable Plaque